Root Skewing-Associated Genes Impact the Spaceflight Response of Arabidopsis thaliana - Califar, Brandon; Sng, Natasha J.; Zupanska, Agata; Paul, Anna-Lisa; Ferl, Robert J. (Frontiers in Plant Science, 2020)
The observation that plant roots skew in microgravity recently refuted the long-held conviction that skewing was a gravity-dependent phenomenon. Further, spaceflight root skewing suggests that specific root morphologies and cell wall remodeling systems may be important aspects of spaceflight physiological adaptation. However, connections between skewing, cell wall modification and spaceflight physiology are currently based on inferences rather than direct tests. Therefore, the Advanced Plant Experiments-03-2 (APEX-03-2) spaceflight study was designed to elucidate the contribution of two skewing- and cell wall-associated genes in Arabidopsis to root behavior and gene expression patterns in spaceflight, to assess whether interruptions of different skewing pathways affect the overall spaceflight-associated process. SPIRAL1 is a skewing-related protein implicated in directional cell expansion, and functions by regulating cortical microtubule dynamics. SKU5 is skewing-related glycosylphosphatidylinositol-anchored protein of the plasma membrane and cell wall implicated in stress response signaling. These two genes function in different cellular pathways that affect skewing on the Earth, and enable a test of the relevance of skewing pathways to spaceflight physiological adaptation. In this study, both sku5 and spr1 mutants showed different skewing behavior and markedly different patterns of gene expression in the spaceflight environment. The spr1 mutant showed fewer differentially expressed genes than its Col-0 wild-type, whereas sku5 showed considerably more than its WS wild-type. Developmental age played a substantial role in spaceflight acclimation in all genotypes, but particularly in sku5 plants, where spaceflight 4d seedlings had almost 10-times as many highly differentially expressed genes as the 8d seedlings. These differences demonstrated that the two skewing pathways represented by SKU5 and SPR1 have unique and opposite contributions to physiological adaptation to spaceflight. The spr1 response is less intense than wild type, suggesting that the loss of SPR1 positively impacts spaceflight adaptation. Conversely, the intensity of the sku5 responses suggests that the loss of SKU5 initiates a much more complex, deeper and more stress related response to spaceflight. This suggests that proper SKU5 function is important to spaceflight adaptation.